2019
DOI: 10.1007/s00468-019-01837-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bioactive compounds in the biomass of black locust, poplar and willow

Abstract: Key message Liquid chromatography is the main method for assaying bioactive compounds in biomass. Total phenolic content and antioxidant capacity are measured with spectroscopy. Phenolics are the most important bioactive substances in short rotation coppice. Secondary metabolites of black locust, willow and poplar have many different activities. The richest source of bioactive compounds are flowers, bark and buds. Abstract The black locust (Robinia pseudoacacia), willow (Salix spp.) and poplar (Populus spp.) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 113 publications
4
39
1
Order By: Relevance
“…Resveratrol, found in wood in low amounts 0.017 -0.271 g/kg, (Tyśkiewicz et al, 2019)) and other plant materials, has AhR antagonist activity and may be protective against dioxin (AhR-dependent) toxicity (Casper et al, 1999), consistent with the negative correlation observed here. The lower signal of this ion in our samples prevented a more-detailed MS n study, so the assignment is tentative.…”
Section: Molecular Composition Of Wsa and Correlations To Aerosol Prosupporting
confidence: 82%
“…Resveratrol, found in wood in low amounts 0.017 -0.271 g/kg, (Tyśkiewicz et al, 2019)) and other plant materials, has AhR antagonist activity and may be protective against dioxin (AhR-dependent) toxicity (Casper et al, 1999), consistent with the negative correlation observed here. The lower signal of this ion in our samples prevented a more-detailed MS n study, so the assignment is tentative.…”
Section: Molecular Composition Of Wsa and Correlations To Aerosol Prosupporting
confidence: 82%
“…Moreover, poplar is of great interest for future, large-scale biomass production to meet the demands of the bioenergy sector [26], in particular, in the cascade use of biomass in biorefineries. In this case, bioactive substances and other phytochemicals are first extracted and the post-extraction biomass is used for bioenergy production [29]. Poplar biomass can be burned in the form of wood chips, successfully processed to pellets [30] or gasified to obtain good-quality, low-contaminated syngas [31].…”
Section: Introductionmentioning
confidence: 99%
“…Perennial crops, grown on agricultural land and harvested in short rotations, can provide substantial amounts of biomass [1][2][3][4]. Until now, biomass was usually used as energy feedstock and its use for industrial purposes and in integrated biorefineries has only recently been contemplated [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%